Six-Month Follow-Up Results of our Slow Pathway Ablation Applied Cases due to Atrioventricular Nodal Reentrant Tachycardia - Yavuzkir, M.; Uysal, A.; Ozguler, M.; Cakmak, T.; Guler, A.; Harman, M. (Excerpta Medica Inc-Elsevier Science Inc, 2014)
[Abstract Not Available]